P75 nerve growth factor receptors modulate development of GnRH neurons and olfactory ensheating cells - Raucci, Franca; Tiong, Jean D.; Wray, Susan (Frontiers in Neuroscience, 2013)
Temporal and spatial localization of nerve growth factor receptor (p75NGFR) in the developing olfactory system and gonadotropin-releasing hormone-1 (GnRH) system was characterized and its role analyzed using p75NGFR null mice and nasal explants. Prenatally, p75NGFR was expressed by GnRH neurons and olfactory ensheathing cells (OECs). In p75NGFR null mice, no change in the number of GnRH cells was detected as compared to wild-type. However, in null mice, a shift in the distribution of GnRH neurons was found, with a small population of GnRH cells migrating further caudally toward the median eminence. Additionally, a reduction of both GAD67 positive olfactory axons and GFAP positive OEC fibers occurred. Acute administration of a p75NGFR blocker to GnRH cells maintained in vitro increased migration rate, consistent with the change in distribution detected in p75NGFR null mice. Chronic inhibition of p75NGFR caused an attenuation of olfactory axon fasciculation and a decrease in OEC density, again mimicking the changes detected in null mice. However, a reduction in GnRH cell number was found after chronic treatment that not observed in KO animals suggesting indirect changes occur during chronic treatment in vitro and/or a compensatory mechanism occurs in vivo that prevents loss of GnRH neurons in the absence of p75NGFR.